Augmented Reality Immersive Technology for Early Childhood Education (ECE) at Merah Delima ECE, East Kelapa Gading - Adam Arif Budiman; Linda Nur Afifah; Timor Setiyaningsih; Suzuki Syofian; Ferdi Maulana (Fakultas Teknik Universitas Darma Persada, 2026)
Augmented Reality (AR) technology possesses significant potential in enhancing students' cognitive aspects and learning motivation through interactive three-dimensional visualizations. However, the implementation of this technology in Early Childhood Education (ECE) levels still requires deeper exploration, particularly concerning animal recognition materials. This community service activity aims to introduce Augmented Reality technology and analyze the importance of animal recognition through AR for young children at Merah Delima ECE. The method employed is a descriptive qualitative approach to observe children's interactions with AR-based learning media. The results indicate that AR is capable of transforming abstract concepts regarding animal habitats and behaviors into concrete experiences that are easily understood by children in the pre-operational developmental stage. The integration of AR into the ECE curriculum is proven to increase active engagement and memory retention compared to conventional methods such as static picture books. Furthermore, the use of AR supports kinesthetic learning, where children explore digital objects spatially. In conclusion, AR-based animal recognition is crucial for building early digital literacy while simultaneously creating an enjoyable learning environment.